FIRST TRIMESTER MEDICAL ABORTION PRACTICE IN NORTH EAST INDIA - VANREMMAWII,; LALROMAWII,; VANLALHRUAII, (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: This study is to compare the efficacy of Mifepristone combined with Misoprostol (Prostaglandin) administered through vaginal and sublingual route in termination of pregnancy of ≤63 days. Methods: Randomized comparative study comprised of 140 pregnant women of ≤63 days gestational age was conducted at Zoram Medical College, Mizoram. Women in group A received 200 mg of Mifepristone orally on day 1 followed by 800 μg of Misoprostol sublingually 36–48 h later, whereas women in group B received 200 mg of Mifepristone orally on day 1 followed by 800 μg of Misoprostol vaginally 36–48 h later. A 2nd dose of 400 μg Misoprostol was given through the same route if abortion process does not start within 4 h. All women who aborted were seen at follow-up and ultrasound pelvis done to confirm complete expulsion of products of conceptions. Results: The total number of primigravida was 34 (24.3%) and multigravida was 106 (75.7%). Complete abortion was seen in 91.4% and 94.28% of per sublingual and per vaginal route group, respectively (p = 0.51). Failure of abortion was 8.57% and 5.71%, respectively, in per oral and per vaginal route (p = 0.51). Conclusion: Sublingual and per vaginal misoprostol after pre-treatment with mifepristone are both an effective method for termination of pregnancy for gestational age of 63 days or less, but the tolerance for sublingual misoprostol was poorer.